Effects of defined voluntary running distances coupled with high‐fat diet consumption on the skeletal muscle transcriptome of male mice - Afrina Brishti; Sarah J. Johnson; Daniel G. Palmer; Md Obayed Raihan; Lin Yan; Shanon L. Casperson (Physiological Reports)
Abstract Exercise counters many adverse health effects of consuming a high‐fat diet (HFD). However, complex molecular changes that occur in skeletal muscle in response to exercising while consuming a HFD are not yet known. We investigated the interplay between diverse exercise regimes and HFD consumption on the adaptation of skeletal muscle transcriptome. C57BL/6 male mice were randomized into five groups—one sedentary control group and four exercise groups. The exercise groups consisted of an unrestricted running group (8.3 km/day) and three groups that were restricted to 75%, 50%, or 25% of unrestricted running (6.3, 4.2, and 2.1 km/day, respectively). Total RNA was extracted from frozen gastrocnemius muscle for transcriptome analyses. DEG counts were 1347, 1823, 1103, and 1107 and there were 107, 169, 67, and 89 unique genes present in the HFD‐25%, HFD‐50%, HFD‐75%, and HFD‐U, respectively. Comparing exercise groups, we found that exercising at 50% resulted in the most differentially expressed transcripts with the MAPK and PPAR signaling pathways enriched in down‐ and up‐regulated genes, respectively. These results demonstrate that running distance impacts the adaptation of the skeletal muscle transcriptome to exercise and suggest that middle‐distance running may provide the greatest protection against high‐fat diet‐induced stress coupled with exercise.